Answer:
see explanation
Explanation:
1
f(4) means what is the value of f(x) when x = 4
substitute x = 4 into f(x)
f(4) = 2(4) - 5 = 8 - 5= 3
-----------------------------------
2
substitute x = - 1 into g(x)
g(- 1) = 3(- 1)² + 5 = 3(1) + 5 = 3 + 5 = 8
--------------------------------------
3
substitute x = 4 into h(x)
h(4) = 3(4) + 2 = 12 + 2 = 14
--------------------------------------
4
(f + g)(- 2)
= f(- 2) + g(- 2)
= 2(- 2) - 5 + 3(- 2)² + 5
= - 4 - 5 + 3(4) + 5
= - 9 + 12 + 5
= - 9 + 17
= 8
-----------------------------------------
5
(f + h)(2)
= f(2) + h(2)
= 2(2) - 5 + 3(2) + 2
= 4 - 5 + 6 + 2
= - 1 + 8
= 7
-------------------------------------------------
6
(f - g)(- 3)
= f(- 3) - g(- 3)
= 2(- 3) - 5 - (3(- 3)² + 5)
= - 6 - 5 - ( 3(9) + 5)
= - 11 - ( 27 + 5)
= - 11 - ( 32)
= - 11 - 32
= - 43
------------------------------------------------
7
(g + h)(- 2)
= g(- 2) + h(- 2)
= 3(- 2)² + 5 + 3(- 2) + 2
= 3(4) + 5 - 6 + 2
= 12 + 5 - 4
= 17 - 4
= 13